Twinning Involving Primary Maxillary Lateral Incisor - Sharma, Jyoti; Sharma, Bhagwat Swaroop; Upadhyay, Manisha (Journal of College of Medical Sciences-Nepal, 2024)
Developmental anomalies in the hard tissue are seen frequently in dental practice. Gemination and fusion are the most commonly encountered anomalies, and distinction between the two is always difficult. Gemination, also known as double tooth, is an anomaly exhibiting two joined crowns and usually a single root. It represents an incomplete attempt of a single tooth germ to split. It is considered multifactorial in etiology, with genetic and environmental causes. This paper discusses a rare example of bilateral gemination (prevalence 0.04%) of maxillary central incisors with completely separated roots. Multidisciplinary care ensured a successful esthetic and functional outcome.